Folate receptor-β constitutes a marker for human proinflammatory monocytes. Issue 4 (11th July 2014) - Shen, Jiayin; Hilgenbrink, Andrew R; Xia, Wei; Feng, Yang; Dimitrov, Dimiter S; Lockwood, Michael B; Amato, Robert J; Low, Philip S
Abstract : Folate receptor-β mediated targeting of inflammatory monocytes in inflammation. Abstract: Activated macrophages are commonly involved in the pathogenesis of inflammatory and autoimmune diseases and have been frequently reported to overexpress FR-β. Although FR-targeted therapies aimed at eliminating activated macrophages have shown promise for treating inflammatory diseases, little work has been performed to evaluate whether other hematopoietic cells might also express FR-β. Analysis of peripheral blood cells with a mAb to human FR-β reveals that only monocytes express FR-β. Molecular characterization of these circulating monocytes further demonstrates that solely the classic/proinflammatory subset (CD14 high CD16 − ) expresses the FR and that only CD14 high CD16 − FR-β + monocytes also display the ability to bind folate-linked molecules. Confirmation that this subset of monocytes indeed constitutes the proinflammatory subpopulation was obtained by demonstrating coexpression of FR-β with other proinflammatory markers, including CCR2 and HLA-DR. Synovial monocytes from the joints of patients with RA were also shown to express FR-β. As inhibition of the chemotaxis of proinflammatory monocytes into sites of inflammation has been explored frequently as a means of controlling autoimmune diseases, demonstration that FR-β is uniquely expressed on this proinflammatory subpopulation offers a new strategy to suppress migration of inflammatory monocytes into sites of inflammation.